A Profile of the Grammatical Variation in British and American English - Akan, Md. Faruquzzaman (Journal of English Language Teaching and Linguistics, 2017)
This research paper attempts to focus on the main and major differences and idiosyncrasies of grammar and grammar related issues in British and American English. These differences have a great influence on learning and using the English language. In fact, British and American English are one language having two (slightly) different grammars. Although there is a popular notion about American English to be more simplified and flexible, we have to keep it in mind about the subtleties, complexities and identifications too. American English is now different from its British mother and we could say it is more than another dialect due to its importance as well as control over the world affairs at present. The fall of the then USSR, the US popular media, open market, globalization, the internet etc have made American English more powerful than ever before. But still today, the number of British English users is more than that of American English. Sometimes, it is noticed by and large that the misuse and the misconception in handling these two major varieties of English pose various problems. So, the main concern of this current paper is to remove the possible mistakes and confusions about the two different but related varieties of English, specially in most of the areas of grammar, syntax and the like.